A full‐discontinuous Galerkin formulation of nonlinear Kirchhoff–Love shells: elasto‐plastic finite deformations, parallel computation, and fracture applications. (9th July 2012) - Becker, G.; Noels, L.
SUMMARY Because of its ability to take into account discontinuities, the discontinuous Galerkin (DG) method presents some advantages for modeling cracks initiation and propagation. This concept has been recently applied to three‐dimensional simulations and to elastic thin bodies. In this last case, the assumption of small elastic deformations before cracks initiation or propagation reduces drastically the applicability of the framework to a reduced number of materials. To remove this limitation, a full‐DG formulation of nonlinear Kirchhoff–Love shells is presented and is used in combination with an elasto‐plastic finite deformations model. The results obtained by this new formulation are in agreement with other continuum elasto‐plastic shell formulations. Then, this full‐DG formulation of Kirchhoff–Love shells is coupled with the cohesive zone model to perform thin body fracture simulations. As this method considers elasto‐plastic constitutive laws in combination with the cohesive model, accurate results compared with the experiments are found. In particular, the crack path and propagation rate of a blasted cylinder are shown to match experimental results. One of the main advantages of this framework is its ability to run in parallel with a high speed‐up factor, allowing the simulation of ultra fine meshes. Copyright © 2012 John Wiley & Sons, Ltd.